STUDY OF ELECTRON PAIRS BELOW THE Z0 MASS PRODUCED IN PBARP COLLISIONS AT SQUARE-ROOT-S=540 GEV - Bagnaia, P; Banner, M; Battiston, R; Bloch, P; Borer, K; Borghini, M; Burger, J; Cenci, P; Chollet, J; Clark, A; Conta, C; Darriulat, P; et al. (1985)
From an integrated luminosity of ∫Ldt = 116 nb-1, 10events are found which contain an electron pair of mass in the range 12 < Mee < 26 GeV c2 and electron transverse momenta pTe > 5 GeV c. THe sample are described, as well as some featruyres of the The production characteristics of this sample are described, as well as some features of the estimated to be 2.2±0.6 events. The production characteristics of this sample are described, as well as some features of the associated event topology. Comparisons are made with the expectations for such electron pair production from the Drell-Yan mechanism and from the semi-leptonic decay of heavy flavours. © 1985.